2014
DOI: 10.1371/journal.pone.0092312
|View full text |Cite
|
Sign up to set email alerts
|

Seven Day Insertion Rest in Whole Body Vibration Improves Multi-Level Bone Quality in Tail Suspension Rats

Abstract: ObjectiveThis study aimed to investigate the effects of low-magnitude, high-frequency vibration with rest days on bone quality at multiple levels.MethodsForty-nine three-month-old male Wistar rats were randomly divided into seven groups, namely, vibrational loading for X day followed by X day rest (VLXR, X = 1, 3, 5, 7), vibrational loading every day (VLNR), tail suspension (SPD), and baseline control (BCL). One week after tail suspension, rats were loaded by vibrational loading (35 Hz, 0.25 g, 15 min/day) exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…To find out the optimal protocol for mechanical stimuli, previous studies have studied the outcomes of vibration with various frequencies, magnitudes and loading cycles. Several recent findings indicated that intermittent vibration with resting periods had significantly enhanced osteogenic effect on bone formation [22,23]. In the present study, we further explored the underpinning mechanism by which mechanic vibration with various resting days regulates the skeletal homeostasis in an ovariectomy-induced rat model of osteoporosis.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…To find out the optimal protocol for mechanical stimuli, previous studies have studied the outcomes of vibration with various frequencies, magnitudes and loading cycles. Several recent findings indicated that intermittent vibration with resting periods had significantly enhanced osteogenic effect on bone formation [22,23]. In the present study, we further explored the underpinning mechanism by which mechanic vibration with various resting days regulates the skeletal homeostasis in an ovariectomy-induced rat model of osteoporosis.…”
Section: Discussionmentioning
confidence: 83%
“…Findings from previous studies including ours indicated that, compared to continuous vibration, intermittent vibration with resting periods improves the biomechanical properties and microstructure of bones in ovariectomized rats [20e22]. A recently published study showed an optimized whole-body vibration regimen in treatment of osteoporosis in rats with tail suspension, which is consisted of repeated low-magnitude and high-frequency vibrations separated by a 7-day resting period for a 8-week treatment course [23]. However, the effects of different vibration regimens on bone anabolics and expression of osteogenesis-related proteins are largely unknown.…”
Section: Introductionmentioning
confidence: 75%
“…The effect of long‐term cyclic/discontinuous vibration regimen on osteoporotic bone will be tested in the future. According to the promising results of Zhang et al in tail suspension rats, administration of LMHFV with rest day insertion was more effective in improving bone properties . It is also proven by Sen et al that the mechanical efficacy on the differentiation of MSCs can be enhanced by the incorporation of a refractory period into the loading regimen .…”
Section: Discussionmentioning
confidence: 94%
“…Scientists considering OVX as a model to evaluate countermeasures for osteopenia must take into account the possibility that the rapid rate of bone loss may severely challenge the ability of any given therapy to restore the compromised architecture. Perhaps the outcome of this study would have been different with longer trials [19,28,29], earlier interventions [30,31], or refractory periods [32,33] to augment the responsiveness of the skeleton.…”
Section: Discussionmentioning
confidence: 98%